SLC7A11: the Achilles heel of tumor? - Jiang, Yulang; Sun, Mingyu (Frontiers in Immunology, 2024)
The non-natriuretic-dependent glutamate/cystine inverse transporter-system Xc-is composed of two protein subunits, SLC7A11 and SLC3A2, with SLC7A11 serving as the primary functional component responsible for cystine uptake and glutathione biosynthesis. SLC7A11 is implicated in tumor development through its regulation of redox homeostasis, amino acid metabolism, modulation of immune function, and induction of programmed cell death, among other processes relevant to tumorigenesis. In this paper, we summarize the structure and biological functions of SLC7A11, and discuss its potential role in tumor therapy, which provides a new direction for precision and personalized treatment of tumors.